Evaluasi Kinerja Sensor FC-28 Untuk Monitoring Kelembapan Tanah Tanaman Indoor Menggunakan Confusion Matrix - Herva Emilda Sari (Forum Kerjasama Pendidikan Tinggi, 2026)
Technology plays an important role in transforming complex challenges into simpler and more practical processes, including soil moisture monitoring for indoor plants. Soil moisture is one of the most critical factors affecting the survival and growth of indoor plants. However, indoor plant owners often face difficulties in determining the moisture condition of the soil, creating the need for a simple and easy-to-use tool for monitoring soil moisture. The FC-28 soil moisture sensor is designed as a simple drought detection device equipped with an LED indicator to provide information regarding soil moisture conditions. The sensor operates by comparing the detected moisture level with a predefined comparator threshold. When the soil moisture falls below the threshold, the LED indicator turns on, indicating that the soil is dry. Conversely, when the moisture level remains above the threshold, the LED stays off, indicating that the soil is sufficiently moist. This study aims to evaluate the performance of the FC-28 sensor in detecting soil moisture conditions in indoor plants. An experimental approach was employed by conducting tests under dry and wet soil conditions. The sensor detection results were compared with the actual soil conditions (ground truth) using the Confusion Matrix method to obtain accuracy, sensitivity, specificity, and error rate values. The results indicate that the FC-28 sensor can consistently distinguish between dry and wet soil conditions in accordance with the actual conditions observed during the testing scenarios. This study contributes by providing a quantitative performance evaluation of the FC-28 sensor using the Confusion Matrix approach through accuracy, sensitivity, specificity, and error rate parameters for indoor soil moisture monitoring applications. The evaluation results demonstrate a high level of agreement between the sensor outputs and the actual soil conditions within the limited testing scope. These findings suggest that the FC-28 sensor can be utilized as a simple and cost-effective soil moisture monitoring tool for indoor plants under controlled environmental conditions.